2019
DOI: 10.1007/s00068-019-01263-6
|View full text |Cite
|
Sign up to set email alerts
|

Increased risk for postoperative periprosthetic fracture in hip fracture patients with the Exeter stem than the anatomic SP2 Lubinus stem

Abstract: Background The purpose of this study was to compare the cumulative incidence of postoperative periprosthetic fracture (PPF) in a cohort of femoral neck fracture (FNF) patients treated with two commonly used cemented stems: either a collarless, polished, tapered Exeter stem or the anatomic Lubinus SP2 stem. Methods In this retrospective multicenter cohort study of a consecutive series of patients, we included 2528 patients of age 60 years and above with an FNF who were treated with either hemiarthroplasty or to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 36 publications
0
11
0
1
Order By: Relevance
“…Other different studies assessing the revision rates of the CPT implants reported a higher rate of periprosthetic fractures in CPT implants when compared to AS implants. 5,[17][18][19][20] The subsidence mechanism of the CPT implants induces hoop stresses to the cement mantle into the host bone which can act as a wedge, fracturing the femur during a fall. 5,21 Also, in the national register-based study of Kristensen et al, 18 with 20,532 primary cemented bipolar hemiarthroplasties, more periprosthetic fractures were observed in CPT implants.…”
Section: Discussionmentioning
confidence: 99%
“…Other different studies assessing the revision rates of the CPT implants reported a higher rate of periprosthetic fractures in CPT implants when compared to AS implants. 5,[17][18][19][20] The subsidence mechanism of the CPT implants induces hoop stresses to the cement mantle into the host bone which can act as a wedge, fracturing the femur during a fall. 5,21 Also, in the national register-based study of Kristensen et al, 18 with 20,532 primary cemented bipolar hemiarthroplasties, more periprosthetic fractures were observed in CPT implants.…”
Section: Discussionmentioning
confidence: 99%
“…Analysis of the cumulative incidence showed that Vancouver B fractures accounted for 6 of the 11 fractures, with the remaining 5 fractures occurring well distal to the stem. Although various studies have demonstrated an association between collarless, polished tapered stems and Vancouver B periprosthetic fractures 25,28,30 , no association has been made between the type of stem and the occurrence of Vancouver C fractures 31 . The increased incidence of Vancouver C fractures in the present study was likely indicative of the tendency to reserve the use of cemented stems for elderly patients or those with poor bone quality, and less directly attributable to the choice of stem 21 .…”
Section: Discussionmentioning
confidence: 99%
“…Theoretically, polished tapered stems, which are designed to subside within their cement mantle, may have similar mechanics to tapered uncemented stems that are more susceptible to fracture in the presence of hip trauma. The subsidence may create an axial load, resulting in a Vancouver B periprosthetic fracture (i.e., a fracture around the stem) 28,29 . In the present study, there were 11 cases of periprosthetic fractures, which was higher than the incidence of periprosthetic fractures reported in other studies of primary THAs with Exeter stems and higher than the 10-year cumulative incidence of postoperative periprosthetic fracture reported in the Mayo registry (1.6%) 12 .…”
Section: Discussionmentioning
confidence: 99%
“…In a cohort comparison of patients aged older than 60 years with femoral neck fracture, patients with a CB Lubinus SP II stem experienced a five-to 16-fold reduction in PFF risk versus a comparable PTS stem group with either an Exeter (Stryker, USA) or CPT stem (Zimmer Biomet). 30,31 Compared to PTS stems, CB stems are more heterogeneous in design, so generalizations across the CB group are difficult. In particular, registry studies do not distinguish between CB stem subtypes in terms of geometry and cement mantle thickness.…”
Section: Cb Stemsmentioning
confidence: 99%